Civil Society as the Fifth Estate: Civil Society, Media Reform and Democracy in Korea - Kwak, Ki-Sung (Television, Regulation and Civil Society in Asia, 2002)
Since the Korean War (1950-53), South Korea (hereafter Korea) has undergone a series of political changes. The move towards democratisation was largely spurred on by the demonstrations and riots occurring throughout the 1980s. In 1987 massive demonstrations forced the then President Chun DooHwan to call a new presidential election, and President-elect Rho Tae-Woo to implement more social reforms. The notion of civil society in Korea has been a relatively new concept until very recently, mainly because it has not achieved wide recognition from the public, media or the state. The development of a people’s movement advocating democracy could be said to be the foundation of ‘civil society’ in Korea.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Corée du Sud (corpus analysé); _Nettoyé

Television in the Formation of Civil Society: The Role of a Non- Controversial Public Space in Hong Kong - Lee, Paul S. N. (Television, Regulation and Civil Society in Asia, 2002)
Television first appeared in Hong Kong in 1957. It was a cable television service run by the Rediffusion Company which had operated a highly successful wired sound broadcasting service since 1949. Hong Kong was the first British colony to have television. But the Rediffusion television service was very expensive. Its monthly subscription fee was HK$55. In 1958, a technical worker’s monthly wages were HK$360 and an unskilled worker earned only HK$75 (Hong Kong Government 1959: 32). A year before the introduction of free-to-air television in 1967, Rediffusion television had only 67,000 subscribers (Hong Kong Government 1967: 206). Thus before 1967 television was an elite medium and its social impact was minimal.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé

Out of Reach: Television, the Public Sphere and Civil Society in the Philippines - Santos, Josefina M. C. (Television, Regulation and Civil Society in Asia, 2002)
In the uprising of 16-20 January 2001, which ousted former Philippine President Joseph Estrada from power, two forces stood out as pivotal: television (specifically the coverage of the impeachment trial which was the centre of public attention) and civil society (which was instrumental in the uprising itself). In this chapter I argue that notwithstanding the central importance of television in this most recent national political change, the regulation of the sector and its long-term associations with crony capitalism have established barriers to civil society finding its voice on television.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Philippines (corpus analysé); Philippines (lieu de production du savoir); _Nettoyé

Changing Contexts, New Texts: ‘‘Inserting’’ TV into the Transforming Text of Post-1980 Bengali Cinema - Gooptu, Sharmistha (Television in India: Satellites, Politics and Cultural Change, 2008)
This chapter analyses a profound transformation of Bengali regional-languagecinema since the early 1980s, a transformation that fundamentally changedthe industry and one that can arguably be attributed at least partly to thecreation of a Bengali television-watching public in the same period. Itfocuses on a trend that emerged in mainstream Bengali cinema during the1980s and was sustained thereafter, and brought into prominence a newconfiguration of elements previously marginal to Bengali films. This trans-formation was to do with mainstream Bengali cinema’s increasing adaptation of what are commonly known as the ‘‘masala’’ or ‘‘formula’’ elementsof Bombay cinema such as racy dialogues, stereotypical villainous char-acters, stylized fights and song-and-dance sequences. This new genre, whichhas commonly been discredited as the Bengali film industry’s totally unim-aginative imitation of the popular Hindi-language cinema of Bombay,completely altered what had been the dominant aesthetic of Bengali cinematill about the mid-1970s. Until this point, Bengali cinema was marked by itsclose relationship with Bengali literature and a Bengali middle-class worldview, greater realism than Bombay cinema or other mainstream regionalcinemas, and naturalistic acting styles, and was radically transformed by agrowing adoption of the ‘‘formula’’ elements commonly identified withpopular Hindi cinema. Industry sources, however, indicate that this newtrend was successful in boosting the Bengali film industry, which had beenswamped by a severe economic crisis since the 1970s. The industry’s crisiswas caused by a host of factors: the most important of these was the Ben-gali middle-class audience’s shift to television as a result of an increasingly unsatisfactory film-going experience in this period. The creation of a Ben-gali television public in the early 1980s shifted audiences from the cinematheatres, thereby significantly reducing film revenues in Calcutta, until then the prime market for Bengali films.
Keywords: 1-Cinéma; 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Soaps, Serials and the CPI(M), Crickets Beat Them All: Cricket and Television in Contemporary India - Majumdar, Boria (Television in India: Satellites, Politics and Cultural Change, 2008)
The changing relationship between cricket and satellite television in thecontext of the Indian sub-continent has been a subject of considerablescholarly inquiry. That one nourishes the other is well known. However,what is relatively little known is the degree to which this interdependence hasgrown in recent times. So much so that cricket tournaments, or ratherdesignated TV tournaments, are being planned with alacrity by the Board ofControl for Cricket in India (BCCI). Television rights for these overseastournaments/matches spread over the next 4 years had initially generated $219.5 million for the BCCI.1 On the other hand, satellite channels too havestarted planning cricket programming around these tournaments, program-ming expected to generate millions in advertising revenue.2 While theorganization of such big-money events well encapsulates the symbiotic rela-tionship between cricket and satellite television within a burgeoning Indianeconomy, other local/regional dimensions of this relationship are often noless fascinating. Tele-visual hype generated on the occasion of a regionalcricket body election in July 2006 in West Bengal, especially by the multiple 24-hour Bengali news channels, drew attention to the local variant of thestory involving big-money television and even bigger-money sport. Thischapter, on the basis of two distinct case studies – the implications of the tri-nation 1-day series played in Malaysia in September 2006 involving Aus-tralia, West Indies and India, and Television coverage of the Cricket Asso-ciation of Bengal Elections in July 2006 – will comment on the complex andever-changing relationship between cricket and television in India. At thesame time it will attempt to question the rationale behind this growing interdependence and probe what this means for the Indian nation at large.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Inde (corpus analysé); _Nettoyé

India Talking: Politics, Democracy and News Television - Mehta, Nalin (Television in India: Satellites, Politics and Cultural Change, 2008)
After four decades of state monopoly over television Indian viewers gottheir first taste of private television in the early 1990s. By 1998, the first of India’s private 24-hour news channels was on the airwaves and by 2007more than 300 satellite channels were broadcasting into Indian homes. Ofthese, 106 broadcast news in 14 languages and as many as 54 of these were24-hour news channels in 11 languages.1 These are conservative figures thatdo not include many foreign and local cable networks that also broadcastnews.2 Even so, the numbers are a stark illustration of how the Indian statelost control over television broadcasting despite its best efforts to the con-trary. No other country in the world has such a concentration of private news channels as India. The creation of a television public has significantimplications for democracy and this essay focuses on what 24-hour newsmeans for India. It argues that the emergence of television news networkshas greatly enhanced and strengthened deliberative Indian democracy.Commercial mass media stands at the junction of politics and the economy,enabling the entry of citizens onto the stage of politics, while simultaneouslyseeking to appropriate that energy for its own commercial benefit (Rajago-pal, 1999: 133). This is a claim that needs to be differentiated from the usual journalistic self-image of the fourth estate acting as vigilant defenders ofdemocratic ideals. That notion should not be romanticised too muchbecause news production itself is a cultural process that cannot be separatedfrom its social environment. News producers always function under certaininstitutional constraints that are endemic to the news-gathering process.Leftist and liberal scholars of the media differ in their emphasis but allagree that news production is always circumscribed by institutional filters.3News is ‘more a pawn of shared suppositions than the purveyor of selfconscious messages’ (Schudson, 1995: 15). Yet, the media are important,and while it is difficult to draw direct causal linkages, there is no doubt thatthey initiate and create a new sphere of political action.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Inde (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Television in Post-Reform China: Serial Dramas, Confucian Leadership and the Global Television Market - Zhu, Ying (Routledge, 2008)
This book explores the political, economic, and cultural forces, locally and globally that have shaped the evolution of Chinese primetime television dramas, and the way that these dramas in turn have actively engaged in the major intellectual and policy debates concerning the path, steps, and speed of China’s economic and political modernization during the post-Deng Xiaoping era. It intertwines the evolution of Chinese television drama particularly with the ascendance of the Chinese New Left that favors a recentralization of state authority and an alternative path towards China’s modernization and China’s current administration’s call for building a "harmonious society." Two types of serial drama are highlighted in this regard, the politically provocative dynasty drama and the culturally ambiguous domestic drama. The book also provides cross-cultural comparisons that parallel the textual and institutional strategies of transnational Chinese language TV dramas with dramas from the three leading centers of transnational television production, the US, Brazil and Mexico in Latin America, and the Korean-led East Asia region. The comparison reveals creative connections while it also explores how the emergence of a Chinese cultural-linguistic market, together with other cultural-linguistic markets, complicates the power dynamics of global cultural flows.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Culture, Politics, and Television in Hong Kong - Ma, Eric Kit-wai (Routledge, 1999)
Ma looks at the ways in which the identity of Hong Kong citizens has changed in the 1990s especially since the handover to China in 1997. This is the first analysis which focuses on the role, in this process, of popular media in general and television in particular. The author specifically analyses at the relationship between television ideologies and cultural identities and explores the role of television in the process of identity formation and maintenance.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé

Television Regulation and Media Policy in China - Chin, Yik-Chan (Routledge, 2016)
Since the late 1990s, there has been a crucial and substantial transformation in China’s television system involving institutional, structural and regulatory changes. Unravelling the implications of these changes is vital for understanding the politics of Chinese media policy-making and regulation, and thus a comprehensive study of this history has never been more essential. This book studies the transformation of the policy and regulation of the Chinese television sector within a national political and economic context from 1996 to the present day. Taking a historical and sociological approach, it engages in the theoretical debates over the nature of the transformation of media in the authoritarian Chinese state; the implications of the ruling party’s political legitimacy and China’s central-local conflicts upon television policy-making and market structure; and the nature of the media modernisation process in a developing country. Its case studies include broadcasting systems in Shanghai and Guangdong, which demonstrate that varied polices and development strategies have been adopted by television stations, reflecting different local circumstances and needs. Arguing that rather than being a homogenous entity, China has demonstrated substantial local diversity and complex interactions between local, national and global media, this book will be of interest to students and scholars of Chinese media, politics and policy, and international communications.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Taiyu Serial Dramas in Taiwan: A History of Problem-Making - Irene Yang, Fang-Chih (Television Histories in Asia, 2015)
The construction of a problem, be it a crisis or a moral panic, is an attempt of policing and control, for the maintenance of hegemony and authority (Hall et al. 1978 ). A problem emerges as a problem only when it is out of its proper place, just like dirt becomes dirt only when it is not properly placed in the earth. The elimination of dirt is necessary in maintaining the cleanliness of the social order (Douglas 2002 ). In other words, it is the need for a particular social arrangement that constitutes the existence of a problem. Taiyu, the lingua franca of the Taiwanese, became a problem of dialect (called Minnanyu) to be eliminated when the KMT colonial regime moved to Taiwan, building it as a Chinese nation and instituting Mandarin as the national language. Television is central to the building of the Chinese nation. Taiyu serial dramas were broadcast soon after the fi rst network was established in 1962, but have been constructed as the most problematic and debased genre since the early 1970s when the second TV station, CTV (1969), and the third, CTS (1971), were established and used serial drama to compete for profi t. Accusations directed at the poverty of its quality and the vulgarity of the audiences have characterized mainstream criticisms and constructions of Taiyu serial dramas as problems from the 1970s to the present. This chapter investigates not only the how and what but also the why of this problem-construction, as an attempt to understand the power mechanisms at work in struggling for hegemonic control. It charts two historical moments – the 1970s and from the 1990s to the present – when language has played a signifi cant role in the articulations of serial dramas as problems and explores the changing political, economic and cultural forces that situate them as problems worthy of discussion. I argue that the history of this problem-making demonstrates the centrality of Chinese culture in political domination through cultural means, with ethnic/class politics playing a central role in the maintenance of a hierarchical social order. In the 1970s, Chinese culture was used to create ethnic/class divisions within Taiwan while simultaneously creating the illusion of a symbolic whole under the name of the Republic of China. However, since the 1990s, and intensifying after the 2000s, with the entanglement of democratization and neoliberalization in Taiwan and the rise of China, the ethnic/class tension is not just complicated by confl icted national identifi cations and Chinese culturepromoted by both the KMT Party’s Republic of China and the People’s Republic of China, but also for unifi cation purposes. While democratization, which involved the search for Taiwanese identity, led to the rise of Taiyu-based Hsiangtu drama, the neoliberal defi nition of culture as economic resource, which consecrates Chinese culture through capital investment, facilitates this unifi cation process while creating further ethnic/class/national identity divisions within Taiwan. The result is a disparaging of Taiyu-based culture in general and, in particular, Taiyu serial drama as a problem to be reformed.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Taiwan (corpus analysé); Taiwan (lieu de production du savoir); _Nettoyé

The Television of Intervention: Mediating Patron–Client Ties in the Philippines - Corpus Ong, Jonathan (Television Histories in Asia: Issues and Contexts, 2015)
Similar to the other countries discussed in this volume, elite dominance over mass media has been a main characteristic of Filipino history. Foreign-educated Filipino intellectuals from wealthy families founded the early periodicals that demanded reform and/or independence from Spanish colonization in the late nineteenth century (Anderson 1983 ). Today, ‘old rich’ landowning families own and operate television networks, radio stations, and newspapers not only as part of prestigious and profi table media conglomerates, but also in connection with their interests in industries as varied as oil and agriculture to insurance, shipping, and mining.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Philippines (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Television, Scale and Place-Identity in the PRC: Provincial, National and Global Influences from 1958 to 2013 - Sun, Wanning; Gorfinkel, Lauren (Television Histories in Asia: Issues and Contexts, 2015)
One may argue that Chinese television has already received more than its fair share of attention in the study of Chinese media. As compared with radio and cinema, which developed in the socialist era (1949-78), television has been seen as the dominant medium in the decades of marketization and economic reforms since the late 1970s (Zhu and Berry 2008 ). Television has been studied as a metonym for the ongoing tension and complicity between the Chinese state and the market (e.g., Zhao 1998 ; 2008a) and as a metaphor for the contradictions between a legacy of socialist rhetoric and ethos and a neoliberal market agenda. It is precisely these contradictions that make up what is often referred to as the ‘Chinese characteristics’ (Zhao 2008a; Sun and Zhao 2009 ) of China’s television culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

Reality Television and the Making of Mobile Publics: The Case of Indian Idol - Punathambekar, Aswin (The Politics of Reality Television: Global Perspectives, 2010)
In the summer of 2007, media coverage of Indian Idol-3 focused attention on how people in the Northeast Indian state of Meghalaya cast aside decades-old separatist identities to mobilize support for Amit Paul, a ﬁnalist from the region. While some fans set up websites and blogs to generate interest and support from the rest of the country and abroad, others formed a fan club and facilitated eﬀorts by a range of groups and organizations to sponsor and manage PCOs (public call oﬃces) in diﬀerent parts of Meghalaya, distribute pre-paid mobile phone cards, and set up landline voting booths. Recognizing the ways in which these activities were beginning to transcend long-standing ethnic, religious, linguistic, and spatial boundaries, state legislators and other politicians soon joined the eﬀort to garner votes for Amit Paul, with the chief minister D. D. Lapang declaring Amit Paul to be Meghalaya’s “brand Ambassador for peace, communal harmony and excellence.”1 It seemed that this three-month-long campaign around a reality television program could set the stage for a remarkable refashioning of the socio-cultural and political terrain in Meghalaya. As one commentator remarked:When Meghalaya’s history is written, it could well be divided into two distinct phases – one before the third Indian Idol contest and one after it. A deep tribal-non-tribal divide, punctuated by killings, riots, and attempts at ethnic cleansing, would mark the ﬁrst phase. A return to harmony and to the cosmopolitan ethos of the past would signify the second. The agent of change: Amit Paul, the ﬁnalist of the musical talent hunt on a TV channel.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Tears, Talk, and Play: A Window to Gender and Sexuality on Tamil Television - Vangal, Uma (Channeling Cultures: Television Studies from India, 2014)
Tamil television lends itself to some interesting initiatives in gender empowerment through its programming in 3 categories – fiction, reality, and talent shows. This chapter provides a glimpse into television programmes on leading Tamil channels over the last decade (2000–10) from a gender perspective. Focusing particularly on women and transgender characters/hosts, emotional and psychological quotients of the shows and their audiences, moments of dramatic intensity, the chapter demonstrates how the vernacular televisual representations were quite different from the stereotypical portrayals of the mainstream ‘national’ television, even though the programmes were produced, televised, and received within the broader patriarchal framework of Tamil cultural and political contexts. The chapter, as a whole, intends to look at the production, representation and identification of Tamil television soaps and reality shows as vehicle for spotlighting gender issues and alternative sexualities in the public domain.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

When Live News was Too Dangerous: The Early History of Satellite TV in India - Mehta, Nalin (Channeling Cultures: Television Studies from India, 2014)
A unique confluence of technological, political and economic factors in the 1990s drove the transformative process that led to the battering down of the government’s monopoly over television. By the end of the 1990s, the growing strength of Indian capitalism after the liberalization of the Indian economy and the forces of what Thomas Friedman has called ‘Globalisation 3.0’ allowed Indian entrepreneurs to level the playing field. The Indian state, having embarked on economic liberalization, was forced to adapt to satellite television as an agent of global capitalism it certainly did not give up control over television easily or voluntarily. Operating at the junction of public culture, capitalism and globalization, satellite news networks have had profound implications for the state, politics, democracy and identity formation. Despite all their shortcomings and sensationalism, the emergence of satellite television news networks has enhanced and strengthened deliberative Indian democracy.
Keywords: 1-TV; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Television News and an Indian Infotainment Sphere - Thussu, Daya Kishan (Channeling Cultures: Television Studies from India, 2014)
The exponential growth of television news in India – from one state controlled network until 1991 to more than 100 news channels in 2012 – has transformed broadcast journalism in the country. This proliferation of news networks has intensified competition for audience and advertising revenue, leading to excessive marketization of news, which increasingly veers toward infotainment. The chapter examines the challenges faced by Indian television news – focusing on economic and political dimensions of television news - and its implications for the world’s largest democracy.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (lieu de production du savoir); Inde (corpus analysé); _Nettoyé

TV after Television Studies: Recasting Questions of Audiovisual Form - Roy, Abhijit (Channeling Cultures: Television Studies from India, 2014)
This chapter locates India, and broadly the post-colonial context, within the larger debates concerning television’s audiovisual form and mode of address. It tries to demonstrate that certain key traits in Indian popular performative traditions, representing an ‘alternative’ negotiation with modernity, are somewhat homologous with what western theorists have tried to specify (though in contradicting terms) as the features of televisual mode of address and ‘flow’. The chapter reads the specific imports of this correspondence in histories of Indian television with special reference to a somewhat novel way television has started imagining the nation after liberalization. The significance of the Indian popular film form as lending a major legacy to tele-viewership in India constitutes a major strand of argument.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Copied from Without and Cloned from Within: India in the Global Television Format Business - Thomas, Amos Owen; Kumar, Keval J. (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Television programme format adaptation is becoming an increasingly signiﬁcant phenomenon in India as it is in many other countries with an active domestic television industry. Some obvious successes stand out in recent years, such as Kaun Banega Crorepati, the licensed adaptation of Celador’s global format success Who Wants To Be A Millionaire?, and C.A.T.S., a licensed Hindi version of the US detective series Charlie’s Angels. However, sensitivity to local cultural nuances has been critical to their popular reception by Indian audiences. Yet despite a few high-proﬁle licensed adaptations or copycatting, there are far more instances of unlicensed adaptations or cloning, sometimes subtle, other times not.
Keywords: 1-TV; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); Suède (lieu de production du savoir); _Nettoyé

Globalization and Television: A Study of the Indian Experience, 1990-2010 - Narayan, Sunetra Sen (Oxford University Press, 2013)
This study explores the globalization and liberalization that has occurred in Indian television over the two decades starting from 1990.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Television in Post-Reform Vietnam: Nation, Media, Market - Nguyen-Thu, Giang (Routledge, 2018)
This book explores Vietnamese popular television in the post-Reform era, that is, from 1986, focussing on the relationship between television and national imagination. It locates Vietnamese television in the experiences of everyday life and the prevailing network of power relations resulting from marketization and globalization, and, as such, moves beyond the clichéd assumption of Vietnamese media as a mere propagandist instrument of the party state. With examples from a wide range of television genres, the book demonstrates how Vietnamese television enables novel conditions of cultural oppression as well as political engagement in the name of the nation. In sharp contrast to the previous image of Vietnam as a war-torn land, post-Reform television conjures into being a new sense of national belonging based on an implicit rejection of the socialist past, hopes for peace and prosperity, and anxieties about a globalized future. This book highlights the richness of Vietnam’s current culture and identity, characterized, the book argues, by ‘fraternity without uniformity’.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Australie (lieu de production du savoir); Vietnam (corpus analysé); _Nettoyé

The Little Emperors’ New Toys: A Critical Inquiry into Children and Television in China - Zhao, Bin (Springer, 2013)
Drawing on original research I conducted in the late 1980s, the book argues for a critical approach to the study of children and television. It begins with critical reappraisals of previous empiricist and interpretative studies to set the ground for a different theoretical inquiry which links biography with history. The situated activity of children's television viewing therefore has to be related to the broader historical and cultural formations in post-Mao China. By way of a methodological pluralism of questionnaire survey, in-depth interviews and observation, the book provides the reader with a thorough critical analysis of the rise of the new commercial ethic in Chinese society in general, and in the sector of media and communications in particular, at the very historical turning point of the late 1980s. Soon after that, Deng Xiaoping made his significant tour to south China, reckoning a big step forward towards further liberalization and started to form a brave new world in China ever since.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Pimpin' Ain't Easy: Selling Black Entertainment Television - Smith-Shomade, Beretta E. (Routledge, 2007)
Launched in 1980, cable network Black Entertainment Television (BET) has helped make blackness visible and profitable at levels never seen prior in the TV industry. In 2000, BET was sold by founder Robert L. Johnson, a former cable lobbyist, to media giant Viacom for 2.33 billion dollars. This book explores the legacy of BET: what the network has provided to the larger US television economy, and, more specifically, to its target African-American demographic. The book examines whether the company has fulfilled its stated goals and implied obligation to African-American communities. Has it changed the way African-Americans see themselves and the way others see them? Does the financial success of the network - secured in large part via the proliferation of images deemed offensive and problematic by many black communities - come at the expense of its African-American audience? This book fills a major gap in black television scholarship and should find a sizeable audience in both media studies and African-American studies.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Television in Bangladesh: News and Audiences - Roy, Ratan Kumar (Routledge India, 2020)
This book examines the role of 24/7 television news channels in Bangladesh. By using a multi-sited ethnography of television news media, it showcases the socio-political undercurrents of media practices and the everydayness of TV news in Bangladesh. It discusses a wide gamut of issues such as news making; localised public sphere; audience reaction and viewing culture; impact of rumours and fake news; socio-political conditions; protest mobilization; newsroom politics and perspectives from the ground. An important intervention in the subject, this book will be useful to scholars and researchers of media studies, journalism and mass communication, anthropology, cultural studies, political sociology, political science, sociology, South Asian studies, as well as television professionals, journalists, civil society activists, and those interested in the study of Bangladesh.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Bangladesh (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Producing Domestic Abuse in Pakistani Television: Between Commerce, Ratings and Social Responsibility - Cheema, Munira (Television for Women, 2016)
Before the liberalisation of television in 2000, Pakistan had one terrestrial channel.The Pakistan Television Corporation (commonly known as PTV) had been the statebroadcaster since 1964 and thus PTV content reflected the policies of differentgovernments. Liberal governments relaxed control over gender on screen – womencould be seen without dupatta – while religiously inclined governments brought intheir own agendas with restrictions on appearance of women, such as the dupattapolicy (see, for example, Ali, 1986; Suleman, 1990; Kothari, 2005; Nasir, 2012).1 In2002, the Independent Media Corporation launched its channel Geo News fromPakistan, followed by other networks, marking the formal launch of the policy ofliberalisation of media on television. Presently, five media groups have control of thePakistani media industry, including electronic and print media. These are Inde-pendent Media Corporation, Pakistan Herald Publications, ARY Group, WaqtGroup and Lakson Group (see for example Proffitt and Rasul, 2013). The broad-casting industry in Pakistan follows an advertiser-driven model that is run through asystem of ratings. At the time of the fieldwork reported here (October-April 2011),Media Logic and Gallup were the two operators that determined the popular tastesof consumers through ratings.2
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 5-Auteur.rice PANDC; 5-Autrice; Pakistan (corpus analysé); _Nettoyé

Shaded Lives: African-American Women and Television - Smith-Shomade, Beretta E. (Rutgers University Press, 2002)
Since its invention, television has been one of the biggest influences on American culture. Through this medium, multiple visions and disparate voices have attempted to stake a place in viewer consumption. Yet even as this programming supposedly reflects characteristics of the general American populace, television-generated images are manipulated and contradictory, predicated by the various economic, political, and cultural forces placed upon it. In Shaded Lives, Beretta Smith-Shomade sets out to dissect images of the African American woman in television from the 1980s. She calls their depiction "binaristic," or split. African American women, although an essential part of television programming today, are still presented as distorted and deviant. By closely examining the television texts of African-American women in comedy, music video, television news and talk shows (Oprah Winfrey is highlighted), Smith-Shomade shows how these voices are represented, what forces may be at work in influencing these images, and what alternate ways of viewing might be available. Smith-Shomade offers critical examples of where the sexist and racist legacy of this country collide with the cultural strength of Black women in visual and real-lived culture. As the nation's climate of heightened racial divisiveness continues to relegate the representation of Black women to depravity and display, her study is not only useful, it is critical.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Is She Strong or Just a B!@*#? Discussion of Black Women's Anger in the Reality Show Bad Girls Club - Goldman, Adria Y. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
It is near impossible to have a discussion of black women in reality television without mentioning the infamous Angry Black Woman (ABW). In fact, some critiques have argued reality television is damaging for black women since many shows focus heavily on this character. 1 This stereotypical characterization of black women is long-standing, due largely to its constant inclusion in media messages. As noted in chapter one, audiences were first officially introduced to her in the 1920s as Sapphire Stevens from the Amos ‘n’ Andy Show ; and her character continued to resurface throughout the years, across several different genres. Despite the many time periods through which this image has traveled, the key characteristic of the Sapphire— her unexplainable anger and aggression— seem to resonate in many modern day images of black women.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

The A to Z of African-American Television - Fearn-Banks, Kathleen (Scarecrow Press, 2009)
From Amos 'n' Andy to The Jeffersons to Family Matters to Chappelle's Show, this volume covers it all with entries on all different genres_animation, documentaries, sitcoms, sports, talk shows, and variety shows_and performers such as Muhammad Ali, Louis Armstrong, Bill Cosby, and Oprah Winfrey. Additionally, information can be found on general issues, ranging from African American audiences and stereotypes through the related networks and organizations. This book has hundreds of cross-referenced entries, from A to Z, in the dictionary and a list of acronyms with their corresponding definitions. The extensive chronology shows who did what and when and the introduction traces the often difficult circumstances African American performers faced compared to the more satisfactory present situation. Finally, the bibliography is useful to those readers who want to know more about specific topics or persons.
Keywords: 1-TV; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Pretty Liar: Television, Language, and Gender in Wartime Lebanon - Khazaal, Natalie (Syracuse University Press, 2018)
"Pretty Liar" explores the rise of language and gender politics on Lebanese television to tell the untold story of the co-evolution of Lebanese television and its audiences and how the civil war of 1975-1991 affected that co-evolution. The shift in public interest in television has been widely acknowledged and interpreted within an institutional context as a victory of the neo-liberal entrepreneurship of a new, agile brand over the government inefficiency of Lebanon's national station, Télé Liban. Yet, the role of the Lebanese Civil War in reshaping national television and broadcasting in Arab media following the emergence of the Lebanese Broadcasting Company in 1985 has been unexplored. Based on empirical data and grounded in theory by Arab and global researchers, "Pretty Liar" offers textual analyses of five Lebanese fictional series, three major and several additional periodicals, and nine literary works, and provides context from unscripted interviews with television administrators, anchors, actors, and freelance contributors, print journalists, and audience members. Khazaal seeks to offer new insight into how entertainment television became a site for politics and political resistance, feminism, and the cradle for post-war Lebanon due to the shift in practices and standards of legitimacy. The history of television in Lebanon is not merely the history of technology and business, Khazaal argues, but rather the history of a people and their continuing quest for a responsive television even during times of civil unrest.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Liban (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Telly-Guillotined: How Television Changed India - Shah, Amrita (SAGE Publications India Pvt, Ltd., 2019)
Fist-fights in television studios, dwindling media autonomy, sensationalism, fake news, religious hate, abusive trolls, political spin ... How did we get here? Three decades ago, before economic liberalization, came the expansion and privatization of Indian television. Technological innovation and easing of government controls offered the prospect of journalistic independence, artistic creativity and an empowered citizenry. This was rendered illusory by runaway growth and untrammelled commercialization. In that thwarted promise of the late 20th century lie the seeds of Indian democracy's current crisis. Telly-Guillotined: How Television Changed India tells the story of how technology was usurped, first by propagandists, then by the market. Going behind the scenes of the world′s greatest media explosion, this book describes the impact of consumerism on the newsroom, the shaping of a new cultural politics and the rise of a new politics of seduction. In a landscape of technological innovation, blurred boundaries and sensory overload, Amrita Shah paints a picture of the Fourth Estate′s challenging future.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Muy buenas noches: Mexico, Television, and the Cold War - Gonzalez de Bustamante, Celeste (Nebraska Paperback, 2013)
By the end of the twentieth century, Mexican multimedia conglomerate Televisa stood as one of the most powerful media companies in the world. Most scholars have concluded that the company’s success was owed in large part to its executives who walked in lockstep with the government and the Partido Revolucionario Institucional (PRI), which ruled for seventy-one years. At the same time, government decisions regulating communications infrastructure aided the development of the television industry. In one of the first books to be published in English on Mexican television, Celeste González de Bustamante argues that despite the cozy relationship between media moguls and the PRI, these connections should not be viewed as static and without friction. Through an examination of early television news programs, this book reveals the tensions that existed between what the PRI and government officials wanted to be reported and what was actually reported and how. Further, despite the increasing influence of television on society, viewers did not always accept or agree with what they saw on the air. Television news programming played an integral role in creating a sense of lo mexicano (that which is Mexican) at a time of tremendous political, social, and cultural change. At its core the book grapples with questions about the limits of cultural hegemony at the height of the PRI and the cold war.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Mexique (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Prioritized: The Hip Hop (Re)Construction of Black Womanhood in Girlfriends and the Game - Lewis, Nghana (Watching While Black, 2012)
Why is it important that a Black woman created, wrote for, and co-produced¹ two highly-regarded television situation comedies that engaged a variety of Black women’s health issues while at the same time these issues were being reduced, simplified, or altogether ignored in mainstream American hip hop? Mara Brock Akil tacitly responded to this question when asked why four episodes of the third season of Girlfriends (2000–2008), the situation comedy she created and co-produced for UPN, addressed the HIV/AIDS crisis among Black women in America. “I have things I want to say,” explained Brock Akil, “about bridging television’s gap between
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

“Hey, Hey, Hey!”: Bill Cosby’s Fat Albert as Psychodynamic Postmodern Play - Russworm, TreaAndrea M. (Watching While Black, 2012)
Although the cartoon series Fat Albert and the Cosby Kids (CBS, 1972–1984) averaged only nine new episodes a year during its twelve-year run (compared to a more standard production cycle of twenty-five to sixty new episodes a year for other cartoons), the show remained a highly popular option for young viewers on late Saturday mornings. By the time of the series’ network premiere in 1972, the cartoon’s animated African American stars—Weird Harold, Dumb Donald, Fat Albert, Rudy, Mushmouth, Bucky, Russell, and Bill—were familiar and recognizable to American audiences as originating from Bill Cosby’s boyhood community of North
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Politics After Television: Hindu Nationalism and the Reshaping of the Public in India - Rajagopal, Arvind (Cambridge University Press, 2001)
In January 1987, the Indian state-run television began broadcasting a Hindu epic in serial form, The Ramayana, to nationwide audiences, violating a decades-old taboo on religious partisanship. What resulted was the largest political campaign in post-independence times, around the symbol of Lord Ram, led by Hindu nationalists. The complexion of Indian politics was irrevocably changed thereafter. In this book, Arvind Rajagopal analyses this extraordinary series of events. While audiences may have thought they were harking back to an epic golden age, Hindu nationalist leaders were embracing the prospects of neoliberalism and globalisation. Television was the device that hinged these movements together, symbolising the new possibilities of politics, at once more inclusive and authoritarian. Simultaneously, this study examines how the larger historical context was woven into and changed the character of Hindu nationalism.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Manufacturing the Gang: Mexican American Youth Gangs on Local Television News - Tovares, Raul Damacio (Greenwood Publishing Group, Incorporated, 2002)
Coverage of Mexican-American youth gangs has been a staple of local television news in the United States for decades, and its form and content have come to embody many journalistic cliches: the rising tide of violence, the spread of drug addiction, the alienated minority youth. But as this bold new study argues, these stories contain gross exaggerations that lead to the reinforcement of stereotypes about Mexican-American young people and the Mexican-American community in general. Indeed, the police and community leaders greatly influence the content of this coverage by deciding what information to make available to the news media, while reporters select certain sources and ignore others, thus slanting the story even further. Source: Publisher
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; États-Unis (lieu de production du savoir)

Television, Nation, and Culture in Indonesia - Kitley, Philip (Ohio University Press, 2014)
The culture of television in Indonesia began with its establishment in 1962 as a public broadcasting service. From that time, through the deregulation of television broadcasting in 1990 and the establishment of commercial channels, television can be understood, Philip Kitley argues, as a part of the New Order’s national culture project, designed to legitimate an idealized Indonesian national cultural identity. But Professor Kitley suggests that it also has become a site for the contestation of elements of the New Order’s cultural policies. Based on his studies, he further speculates on the increasingly significant role that television is destined to play as a site of cultural and political struggle.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Indonésie (corpus analysé); _Nettoyé

Consuming Halal Turkish Television in Indonesia: A Closer Look at the Social Responses Towards Muhteşem Yüzyıl - Rakhmani, Inaya; Zakiah, Adinda (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter unpacks the tension between secular, modern values and conservative, Islamic interpretations within the Indonesian middle class by taking the consumption of Turkish popular cultural products as a case. The chapter explicates the social responses towards the first Turkish television drama aired on terrestrial, private television in Indonesia: The Magnificent Century (Muhtesṃem Yüzyıl/Abad Kejayaan). This chapter understands the reproduction of secular and conservative Islamic values, while in contestation, as a response to broader global, market-capitalist developments. It finds that in response to audience criticism regarding the “un-Islamic” portrayal of the epoch in the drama—specifically the depiction of women as concubines—television stations enlisted the services of Muslim clerics to correct or justify the representation of historical facts. This reveals that market-driven self-censorship has opened up ways for Muslim clerics to influence television content. As such, the chapter argues that market-capitalist forces discursively use Islamic authority as a way to legitimise the halal consumption of Turkish drama among Indonesian Muslim audience at the expense of programme diversity.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Indonésie (corpus analysé); Indonésie (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

Critical Distance - Critical Distance (Critical Distance)
Back in 2009, Critical Distance was founded to answer the question: “Where is all the good writing about games?” Our goal for the last 10 years has always been to facilitate dialogue. Through roundups, roundtables, podcasts, and critical compilations, we provide one place where all the most important discourse is collected together. We aim to build a foundation for ongoing conversations between developers, critics, educators and enthusiasts about critical issues in games culture. We are a compendium of the most incisive, thought-provoking, and remarkable discussion in and around games, keeping it archived for years to come. Our work has helped new writers to find their voice, educators to find resources to help their students develop critical thinking, and developers to become more reflective in their design practice.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 5-Auteur.rice PANDC; _Nettoyé

Video Game History and the Fact of Blackness - Russworm, TreaAndrea M. (ROMchip, 2019)
Video games studies, including many of our most inspired written accounts of video game history, is very white. Stories about US video game pioneers, from engineers and designers to early adopters and arcade patrons, tend to be mostly about the white men who created, consumed, and periodically saved the industry. Even now that game history is on the verge of becoming as queer and ostensibly nonconformist as some aspects of its games and culture are theorized to be, these new avenues of critical investigation speak most directly to a queer mainstream that has always been constructed as white. Although there is much to be inspired by in the proliferation of emergent video game histories that are more gender-inclusive, trans, or so-called diverse, with few exceptions these progressive accounts still tend to be White. White. White. Black designers, players, blerds, and technocrats have been excluded from the canon of old and new video game histories in much the same way Frantz Fanon theorized that blackness functions as a fact: an outwardly defined pejorative social inscription that justifies its alienation and exclusion.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

A Critical Cultural History of Online Games in China, 1995–2015 - Chew, Matthew M. (Games and Culture, 2016)
This study critically assesses the Chinese online games industry through problematizing the creativity of Chinese games. I find that between 1995 and 2001, Chinese online games were mostly developed by amateurs, noncommercial, and considerably creative. Between 2002 and 2005, industrial growth allowed some room for local creativity despite commercialization and dominance of imported games. Current scholarly, business, and media discourses unfairly ignore creativity in these first two periods and yet praise the Chinese game industry’s commercial success since the late 2000s. I challenge these discourses by illustrating that between 2006 and early 2009, a new, ethically dubious, and uniquely Chinese business model emerged, became domestically dominant, and quietly and profoundly impacted on global online game design. From mid-2009 to 2015, there is ongoing corporatization based on the dubious Chinese business model on the one hand, and a reemphasis on creativity motivated by browser and mobile game formats on the other.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Games With a Continuum: Globalization, Regionalization, and the Nation-State in the Development of China’s Online Game Industry - Jiang, Qiaolei; Fung, Anthony Y.H. (Games and Culture, 2019)
As a case study, this article examines the development of China’s online game industry and how China responds to the forces of globalization. Based on in-depth interviews, ethnographic research, and the analysis of archive documents from the past few years, this study identifies China’s evolving strategy of neo-techno-nationalism. In the Chinese context, this national strategy manipulates technology to create a version of popular nationalism that is both acceptable to and easily censored by the authorities. Therefore, cultural industries that adopt this strategy stand a good chance of prevailing in the Chinese market. This success explains why the regional competitors of Chinese online games—Korean games—are more successful in China than most of their Western counterparts. By providing a snapshot of the current ecology of China’s online game industry, this article also discusses the influence of regional and global forces in a concrete context and argues that the development of China’s online game industry depends more on political factors than economic factors.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

The Iconography of Chicano Self-Determination: Race, Ethnicity, and Class - Goldman, Shifra M. (Art Journal, 1990)
In several cities in the Southwest and Midwest with sizable enclaves of Chicanos, there are to be found considerable numbers of images that have become leitmotifs of Chicano art. In their ubiquity, these motifs demonstrate that the Chicano phase of Mexican-American art (from 1965 to the 1980s) was nationally dispersed, shared certain common philosophies, and established a network that promoted a hitherto nonexistent cohesion. In other words, it was a movement, not just an individual assembly of Mexican-descent artists. In what follows, Chicano art is examined as statements of a conquered and oppressed people countering oppression and determining their own destiny, though not all the producers of these images necessarily saw their production in the political way they are framed below. Examples have been chosen specifically to show how, in response to exploitation, artists have taken an affirmative stance celebrating race, ethnicity, and class.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Painting, Literature and Film in Colombian Feminine Culture, 1940-2005: Of Border Guards, Nomads and Women - Martin, Deborah (Cambridge University Press, 2013)
This book explores crucial moments in the emergence of feminine culture in Colombia hitherto unexamined in English-language criticism through an examination of the work of ground-breaking artist Débora Arango, best-selling novelist Laura Restrepo, and three generations of documentary filmmakers.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

The Race Card: from Gaming Technologies to Model Minorities - Fickle, Tara (New York University Press, 2020)
This book uncovers popular games' key role in the cultural construction of modern racial fictions. It argues that gaming provides the lens, language, and logic - in short, the authority - behind racial boundary making, reinforcing and at times subverting beliefs about where people racially and spatially belong. It focuses specifically on the experience of Asian Americans and the longer history of ludo-Orientalism, wherein play, the creation of games, and the use of game theory shape how East-West relations are imagined and reinforce notions of foreignness and perceptions of racial difference.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

White Out: the Continuing Significance of Racism. - Doane, Ashley W; Bonilla-Silva, Eduardo (Taylor and Francis, 2013)
What does it mean to be white? This remains the question at large in the continued effort to examine how white racial identity is constructed and how systems of white privilege operate in everyday life. White Out brings together the original work of leading scholars across the disciplines of sociology, philosophy, history, and anthropology to give readers an important and cutting-edge study of ""whiteness""
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Discours sur le colonialisme ; suivi de Discours sur la négritude - Césaire, Aimé (2015)
Comme naguère Jean-Jacques Rousseau dénonçait le scandale d'une société fondée sur l'inégalité, avec la même clarté, et un bonheur d'écriture que seule peut inspirer la passion du juste, Aimé Césaire prend ses distance par rapport au monde occidental et le juge. Ce discours est un acte d'accusation et de libération. Sont assignés quelques ténors de la civilisation blanche et de son idéologie mystifiante, l'Humanisme formel et froid. En pleine lumière sont exposées d'horribles réalités : la barbarie du colonisateur et le malheur du colonisé, le fait même de la colonisation qui n'est qu'une machine exploiteuse d'hommes et déshumanisante, une machine à détruire des civilisations qui étaient belles, dignes et fraternelles. C'est la première fois qu'avec cette force est proclamée, face à l'Occident, la valeur des cultures nègres. Mais la violence de la pureté du cri sont à la mesure d'une grande exigence, ce texte chaud, à chaque instant, témoigne du souci des hommes, d'une authentique universalité humaine. Il s'inscrit dans la lignée de ces textes majeurs qui ne cessent de réveiller en chacun de nous la générosité de la lucidité révolutionnaires. Le Discours sur le colonialisme est suivi du Discours sur la Négritude, qu'Aimé Césaire a prononcé à l'Université Internationale de Floride (Miami), en 1987.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

La (dé)mythification de l’artiste colombien MIGUEL ÁNGEL ROJAS ET JOSÉ ALEJANDRO RESTREPO - de la Cruz Lichet, Virginia (Revue Proteus, 2019)
Depuis quelques décennies, certains artistes colombiens cherchent à repenser ce que peut être aujourd’hui l’identité colombienne, et plus concrètement celle de l’artiste. Au-delà du stéréotype de ce qu’est le « Colombien » vu de l’extérieur, au-delà d’une histoire coloniale – et toutes ses problématiques – commune aux pays d’Amérique latine, ainsi que d’une histoire récente plus particulière connue pour son extrême violence, nous pouvons affirmer que l’identité colombienne est le résultat d’identités multiples, diverses et variées. Par ailleurs, il existe un dénominateur commun qui peut la définir car elle s’est construite durant ces deux derniers siècles à partir d’un concept : celui de « l’hybridité ».
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Réactualiser l’archive, réécrire l’histoire: Des pratiques artistiques décoloniales - De Souza, Fabiana (Revue Asylon(s), 2018)
Réfléchissant comme l’a fait Fanon, à partir de « la condition ontologique-existentielle racialisée du sujet colonisé », cet article se propose d’analyser des pratiques artistiques contemporaines qui cherchent à réactualiser le statut de l’archive. En faisant appel à la pensée décoloniale latino-américaine, nous allons voir comment des artistes affectés par des processus de « sélection et de répression » - enracinés dans les expériences subjectives et culturelles des populations regroupées sous le terme Sud global - ont ré-apprivoisé les archives, donnant lieu à des pratiques artistiques décoloniales ou pratiques artistiques de « ré-invention » de soi.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Proposition avant-garde: a view from the South - Kapur, Geeta (Art journal / College Art Association of America., 2018)
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

El color de la razón: racismo epistemológico y razón imperial - Castro-Gómez, Santiago; Eze, Emmanuel Chukwudi; Henry, Paget (Ediciones del Signo, 2014)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Musee Migrant – MuMi - Clériga Morales, Deyanira; Valenzuela Arámburo, Pável; Ledón Pereyra, Aldo Jorge (revue Periferias, 2019)
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

L’hybris du point zero. Science, race et Lumières en Nouvelle-Grenade (1750-1816) - Castro-Gómez, Santiago (Revue d'Études Décoloniales, 2017)
Ce texte est la traduction de l’introduction au livre de Santiago Castro-Gómez, La hybris del punto cero: ciencia, raza e ilustración en Nueva Granada (1750-1816), Bogota: Ed. Pontificia Universidad Javeriana, 2005.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Le postcolonial en Amérique latine: débats contemporains - Gómez-Muller, Alfredo (2016)
"En Amérique latine comme ailleurs, la critique postcoloniale apparaît comme une condition pour le renouvellement des dialogues interculturels orientés vers la construction d'une modernité alternative, ou d'une vraie postmodernité, fondée sur une autre manière d'habiter la terre, moins dévastatrice pour la nature comme pour les humains. Reprenant d'une manière inédite la perspective ouverte au XXe siècle par des auteurs comme José Carlos Mariátegui, Alberto Flores Galindo, Pablo González Casanova ou René Zavaleta, les études postcoloniales latino-américaines contribuent à la critique d'un modèle culturel, social et politique fondé sur le clivage traditionnel entre la " civilisation " et la "barbarie". Articulée initialement par un versant de la modernité européenne qui trouvera au XVIIIe siècle une forme systématique dans l'anthropologie des Lumières (M. Duchet), cette dichotomie a été au départ la matrice idéologique de la domination coloniale européenne, et, plus tard, de celle des nouvelles élites " républicaines " attelées à la tâche de construire l'unité sociale et politique sur la base du modèle européen de l'État-nation. Au XIXe siècle et durant une bonne partie du XXe, l'unité de la "Nation" est imaginée de telle manière qu'elle implique l'exclusion de la différence culturelle dans l'espace public. Or, depuis les quatre dernières décennies, les nouvelles formes de la mobilisation indienne et la renaissance des identités afro-américaines participent à la crise des modèles identitaires établis et au surgissement, dans divers domaines du culturel et du politique, de manières inédites d'imaginer l'identité (subjective, sociale, culturelle, nationale) et d'assumer la diversité culturelle (inter-culturalité, multiculturalismes, indianisation) dans la sphère publique. Le présent ouvrage propose un aperçu des problématiques, recherches et discussions actuelles sur le postcolonial en Amérique latine, en prenant comme fil conducteur les processus de reconfiguration identitaire liés à l' " émergence indienne " et au renouveau actuel des identités afro-américaines."--Page 4 de la couverture.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Pensée critique latino-américaine : de la philosophie de la libération au tournant décolonial - Hurtado López, Fátima (Cahiers des Amériques latines, 2009)
Cet article est une introduction à la pensée critique latino-américaine, de la philosophie de la libération au tournant décolonial proposé par le groupe de recherche pluridisciplinaire Modernité/Colonialité. Dans un premier temps sont présentées les principales contributions de la philosophie de la libération en tant que pensée critique latino-américaine. Est abordée ensuite la question de la pertinence actuelle des motivations et des inquiétudes initiales de la philosophie de la libération, ainsi que la pertinence de ses thèses et de ses principales catégories. Puis sont présentées les principales critiques adressées à ce courant de pensée en quarante ans d’existence. Enfin est introduit le tournant décolonial du groupe Modernité/Colonialité. L’accent est mis sur la notion de pluriversalité que proposent les penseurs critiques latino-américains présentés dans cet article.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Feminismos disidentes en América Latina y el Caribe // Féminismes dissidents en Amérique latine et aux Caraïbes - Curiel, Ochy; Falquet, Jules; Masson, Sabine (Editions Antipodes, 2005)
La idea de elaborar un número sobre las luchas de las mujeres y las feministas en América Latina y el Caribe surgió de un encuentro entre Sabine Masson (Suiza), Jules Falquet (Francia) y Ochy Curiel (República Dominicana), cuyos caminos se cruzaron en el continente latinoamericano por razones personales y políticas. Debatimos y reflexionamos juntas sobre la cuestión de las barreras de "raza" y de clase que nos atraviesan a las feministas de diferentes partes del mundo, y que son en particular el reflejo de las relaciones de dominación entre el Sur y el Norte. Precisamente por estas barreras, las experiencias políticas y el trabajo de construcción colectiva de muchas feministas y mujeres, especialmente de América Latina y el Caribe, siguen siendo desconocidas para la mayoría de las feministas de otras latitudes, y de poco interés para las revistas académicas feministas de los países ricos. Oponerse a esta invisibilización y contribuir, aunque sea a nivel experimental y muy modesto, a la deconstrucción de estas barreras, fue nuestra principal motivación para organizar este número en una revista francófona como Nouvelles Questions Féministes. Sin embargo, el trabajo de coordinación presentó importantes contradicciones: primero, entre nosotros mismos. En primer lugar, tuvimos que reconocer e integrar las diferencias y similitudes de nuestras respectivas posiciones, para llegar a un consenso que nos permitiera desarrollar esta cuestión juntos. En segundo lugar, nos enfrentamos al riesgo de reproducir una vez más el saqueo de los conocimientos de las mujeres indias, afrodescendientes y mestizas latinoamericanas y caribeñas por parte de los "expertos del Norte". Los textos se traducirían al francés, lo que significaría que una ínfima minoría de mujeres latinoamericanas y caribeñas tendría acceso a ellos, mientras circulaban por Europa, enriqueciendo una vez más el conocimiento de las mujeres de los países ricos con el trabajo, las luchas, las historias y los escritos de las mujeres de los países pobres. Ante este problema, decidimos que la publicación de este número fuera acompañada de una versión en español, con el objetivo de hacer circular y compartir esta producción intelectual en América Latina y el Caribe L’idée de faire un numéro sur les luttes de femmes et les luttes féministes en Amérique latine et aux Caraïbes a surgi de la rencontre entre Sabine Masson (Suisse), Jules Falquet (France) et Ochy Curiel (République Dominicaine), dont les chemins se sont croisés sur le continent latino-américain pour des raisons personnelles autant que politiques. Nous avons débattu et réfléchi ensemble sur la question des barrières de « race » et de classe qui nous traversent, nous les féministes de différentes parties du monde, et qui sont notamment le reflet des rapports de domination entre le Sud et le Nord. Justement à cause de ces barrières, les expériences politiques et le travail de construction collective de beaucoup de féministes et de femmes, notamment latino-américaines et des Caraïbes, demeurent inconnus de la plupart des féministes d’autres latitudes, et intéressent peu les revues féministes académiques des pays riches. S’opposer à cette invisibilisation et contribuer, même si ce n’est qu’à un niveau expérimental et très modeste, à déconstruire ces barrières, a constitué notre principale motivation pour organiser ce numéro dans une revue francophone comme Nouvelles Questions Féministes . Néanmoins, le travail de coordination présentait d’importantes contradictions : d’abord, entre nous. Pour commencer, nous avons dû reconnaître et intégrer les différences et les similitudes de nos positions respectives, afin de parvenir à un consensus qui nous permette d’élaborer ce numéro ensemble. Ensuite, nous nous confrontions au risque de reproduire encore une fois le pillage des connaissances des femmes indiennes, afro-descendantes et métisses latino-américaines et des Caraïbes par les « expertes du Nord ». Les textes allaient être traduits en français, c’est-à-dire qu’une infime minorité de femmes latino-américaines et des Caraïbes pourrait y avoir accès, pendant qu’ils circuleraient en Europe, enrichissant une fois de plus le savoir des femmes des pays riches à partir du travail, des luttes, des histoires et des écrits des femmes des pays pauvres. Face à ce problème, nous avons décidé que la publication de ce numéro allait s’accompagner d’une version en espagnol, dans le but de faire circuler et de partager cette production intellectuelle en Amérique latine et aux Caraïbes
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Vistazo Crítico 135: Nelson Fory Ferreira: la historia nuestra caballero. - Arcos-Palma, Ricardo (VISTAZOS CRÍTICOS: 20 años de crítica de la cultura y del arte, 2015)
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Critics and the Slippery Terrain of Latinx Art - Dávila, Arlene (Latin American and Latinx Visual Culture, 2019)
When E. Carmen Ramos organized Our America: The Latino Presence in American Art (2013) at the Smithsonian American Art Museum in Washington, DC, art holdings of Latinx artists at the institution were minimal and unbalanced. The museum lacked works by foundational figures; entire groups like Dominican Americans were missing, as were genres like abstract art; and with a collection dominated by colonial and folk art and work by Mexican Americans, it was impossible to produce any comprehensive exhibition of contemporary Latinx art, much less one that represented the diversity of artists and trends. Ramos was one of the few Latinx curators hired in the aftermath of the infamous 1994 “Willful Neglect” report documenting a historical pattern of discrimination at the Smithsonian Institute and calling for the hiring of Latinx curators to help direct the Smithsonian’s priorities in research, collections, and exhibitions.1 Twenty-five years later, this pattern of exclusion continues apace. In 2018, a study by UCLA’s Chicano Studies Research Center found that while the Smithsonian’s Latinx workforce grew from 2.5 percent to 10.1 percent, this growth falls short of representing the growth of the Latinx population, which since 1994 has doubled to 17.8 percent of the total population. In sum, the task of putting a dent in a mostly white canonical art history and collection was a daunting one, and whatever Ramos did would be a politically charged intervention. This would be the first major scholarly survey exhibition of Latinx art, a statement to insert it as central to US art history, and the first major show of its type in a major North American museum in decades.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Metamorphic and Sensuous Brown Bodies: Queer Latina/x Visual and Performance Cultures in San Francisco Strip Clubs, 1960s–1970s - Otálvaro-Hormillosa, Gigi (Latin American and Latinx Visual Culture, 2019)
In the 1960s, topless entertainment became legal in San Francisco, although cross-dressing continued to be criminalized. This article documents queer Latina/x visual and performance cultures of San Francisco’s strip club industry during this critical moment. It employs visual and performance analyses that draw from ethnographic interviews and archival research about three Latinas who performed as exotic dancers during this period, two of whom were out transsexuals: Roxanne Lorraine Alegria, Vicki Starr, and Lola Raquel. Engaging Marcia Ochoa’s notion of “spectacular femininities” and Juana María Rodríguez’s theory of “queer gesture,” the article maps out a queer Latina/x herstoriography about the early days of topless entertainment in San Francisco. It demonstrates how the transgressive practices of these Latina performers enrich genealogies of queer and Latina/x performance and visual cultures since the 1960s. It thus contributes to the expansion and intersection of the fields of performance studies, Latina/x studies, and feminist, gender, and sexuality studies. These fields and their intertwinings offer critical tools to resist the sexism, homophobia, racism, transphobia, and whorephobia that pervade every level of society, as well as the cultural amnesia to which San Francisco has been increasingly prone due to its incessant gentrification and growing technocracy since the early 2010s.RESUMEN Este artículo documenta las culturas visuales y de performance latinas/x queer de los clubes de striptease de San Francisco durante un momento crítico en la historia de la ciudad. En la década de 1960, los shows en topless se legalizaron en San Francisco, aunque el travestismo se continuó criminalizando. Otálvaro-Hormillosa emplea análisis visuales y de performance que se basan en entrevistas etnográficas e investigación de archivo sobre tres latinas que actuaron como bailarinas exóticas durante este período, dos de las cuales reconocían públicamente que eran transexuales: Roxanne Lorraine Alegria, Vicki Starr y Lola Raquel. En diálogo con la noción de “feminidades espectaculares” de Marcia Ochoa y la teoría de “gestos queer” de Juana María Rodríguez, Otálvaro-Hormillosa describe una historiografía latina/x queer propiamente femenina sobre los primeros días del entretenimiento en topless en San Francisco. El artículo demuestra cómo las prácticas transgresoras de estas intérpretes latinas enriquecen las genealogías de las culturas visuales y de performance queer y latinas/x desde los años sesenta. Al hacerlo, contribuye a la expansión e intersección de los campos de los estudios de performance, estudios latinas/x, y estudios feministas, de género y de sexualidad. Estos campos y sus entrecruzamientos pueden ofrecer herramientas críticas para resistir el sexismo, la homofobia, el racismo, la transfobia y la putafobia que permea todos los niveles de la sociedad, así como la amnesia cultural a la que San Francisco ha sido cada vez más propenso debido a su incesante gentrificación y creciente tecnocracia desde principios de los años 2010.RESUMO Este artigo documenta a cultura visual e de performance na indústria de clubes de strip-tease de São Francisco, durante um momento crítico da história da cidade. Nos anos 60, o entretenimento topless se tornou legal em São Francisco, embora a prática do cross-dressing continuasse criminalizada. Otálvaro-Hormillosa emprega análise visual e de performance baseadas em entrevistas etnográficas e pesquisas de arquivos sobre três latinas que se apresentaram como dançarinas exóticas durante esse período, duas das quais eram transexuais: Roxanne Lorraine Alegria, Vicki Starr e Lola Raquel. Engajando a noção de “feminilidades espetaculares” de Marcia Ochoa e a teoria do “gesto queer” de Juana María Rodríguez, Otálvaro-Hormillosa mapeia uma herstoriografia queer latina/x sobre os sobre os primórdios do entretenimento topless em São Francisco. O artigo demonstra como as práticas transgressivas dessas artistas latinas enriquecem as genealogias das culturas visual e de performance queer e latina/x desde os anos 1960. Deste modo, contribui para a expansão e intersecção dos campos de estudos da performance, estudos latinos e estudos feministas, de gênero e sexualidade. Esses campos e seus entrelaçamentos podem oferecer ferramentas críticas para resistir ao sexismo, homofobia, racismo, transfobia e putafobia que permeiam todos os níveis da sociedade, bem como a amnésia cultural para a qual San Francisco tem sido cada vez mais propensa devido à sua gentrificação incessante e crescente tecnocracia desde o início dos anos 2010.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Postcolonial Modernism: Art and Decolonization in Twentieth-Century Nigeria - Okeke-Agulu, Chika (Duke University Press, 2015)
Written by one of the foremost scholars of African art and featuring more than 125 color images, Postcolonial Modernism chronicles the emergence of artistic modernism in Nigeria in the heady years surrounding political independence in 1960.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Visual Disobedience: The Geopolitics of Experimental Art in Central America, 1990-Present - Cornejo, Kency (N.D., 2014)
This dissertation centers on the relationship between art and politics in postwar Central America as materialized in the specific issues of racial and gendered violence that derive from the region's geopolitical location and history. It argues that the decade of the 1990s marks a moment of change in the region's cultural infrastructure, both institutionally and conceptually, in which artists seek a new visual language of experimental art practices to articulate and conceptualize a critical understanding of place, experience and knowledge. It posits that visual and conceptual manifestations of violence in Central American performance, conceptual art and installation extend beyond a critique of the state, and beyond the scope of political parties in perpetuating violent circumstances in these countries. It argues that instead artists use experimental practices in art to locate manifestations of racial violence in an historical system of domination and as a legacy of colonialism still witnessed, lived, and learned by multiple subjectivities in the region. In this postwar period artists move beyond the cold-war rhetoric of the previous decades and instead root the current social and political injustices in what Aníbal Quijano calls the `coloniality of power.' Through an engagement of decolonial methodologies, this dissertation challenges the label "political art" in Central America and offers what I call "visual disobedience" as a response to the coloniality of seeing. I posit that visual colonization is yet another aspect of the coloniality of power and indispensable to projects of decolonization. It offers an analysis of various works to show how visual disobedience responds specifically to racial and gender violence and the equally violent colonization of visuality in Mesoamerica. Such geopolitical critiques through art unmask themes specific to life and identity in contemporary Central America, from indigenous genocide, femicide, transnational gangs, to mass imprisonments and a new wave of social cleansing. I propose that Central American artists--beyond an anti-colonial stance--are engaging in visual disobedience so as to construct decolonial epistemologies in art, through art, and as art as decolonial gestures for healing.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Visionarias de la perspectiva de género en el arte contemporáneo del Caribe colombiano - Flórez, Alexa Cuesta (Memoria y Sociedad, 2017)
La perspectiva de género en el arte del Caribe colombiano se puede contextualizar con el movimiento feminista planetario. La comparación se establece en las creaciones de mujeres artistas de esta región, ya que subvierten, manifiestan y revelan con denotada libertad expresiva, no solamente sus inquietudes intimistas, sino toda una serie de cuestionamientos a las condiciones que culturalmente se le han impuesto a la mujer en el Caribe. Son dos generaciones diferentes; las primeras, analizadas en esta entrega, pueden ser catalogadas como pioneras de la perspectiva de género en el arte colombiano. Las segundas, consolidan problemáticas en apuestas individuales, de manera diaspórica y cada vez más comprometidas con el movimiento social de mujeres. En ambos casos lo hacen a través de las artes visuales, audiovisuales, performáticas e híbridas. Estamos ante artistas vanguardistas, de las artes visuales y performáticas en el Caribe colombiano; preferimos llamarlas, en ambos casos, visionarias. Gender perspective in the Colombian Caribbean art can be contextualized within the worldwide feminist movement. The comparison is established in the artwork of female artists from this region, as they subvert, demonstrate, and reveal with poignant expressive freedom, not only their intimate concerns, but a whole series of questions to the conditions that have been culturally imposed on women in the Caribbean. They come from two different generations. The first generation, analyzed in this installment, can be defined as the pioneers of gender perspective in Colombian art. The second generation consolidates issues through individual pledges in a diasporic way and increasingly committed to the social women’s movement. Both generations do this through performative, hybrid, visual and audiovisual art. These are avant-garde artists of the visual and performative art in the Colombian Caribbean. We prefer to call them, in both cases, visionaries.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

The Limits of Feminism: Decolonizing Women's Liberation/Oppression Theory - Kuumba, Monica Bahati (Race, Sex & Class, 1994)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Revista N'oj Panel on Decolonizing Aesthetics - Latinx Research Center (2020)
The Latinx Research Center's Revista N'oj hosted a round table discussion on Decolonial Aesthetics titled, "Decolonizing Art & Praxis in the Time of Covid-19." The talk included Jesus Barraza, Dr. Guisela Latorre, Dr. Mauricio Barros de Castro, and Dr. Laura E. Pérez. The panel was moderated by Revista N'oj editor, Abraham Ramirez.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Orientalismo, poscolonialidad y conocimientos de otro modo: bases, críticas, silencios y continuidades para una discusión político-cultural en el contexto latinoamericano - Estrada, Edwin Jader Suaza (Revista de Estudiantes de Ciencia Política, 2016)
La perspectiva de la modernidad/colonialidad provee un encuadre alternativo para los debates sobre la modernidad, la globalización y el desarrollo desde la periferia latinoamericana del sistema mundo moderno colonial. Las ideas que se exponen en el presente artículo, proporcionan un guía de lectura frente a los principales rasgos del entramado conceptual que rodea a este lugar de enunciación del conocimiento. La perspectiva modernidad/colonialidad aporta una reflexión sobre la cultura y diferentes planos de la realidad social y política, nutrida en debates académicos sustentados no desde una perspectiva intra-epistémica, como los discursos críticos europeos, sino desde la mirada de los receptores de los supuestos beneficios del mundo moderno. Se presenta así un contexto para interpretar Latinoamérica, entendida más como un espacio epistémico y de producción de conocimiento, que como una región objeto de conocimientos pre-establecidos.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Orientalism - Said, Edward W (Penguin Books, 2019)
A groundbreaking critique of the West's historical, cultural, and political perceptions of the East that is—three decades after its first publication—one of the most important books written about our divided world. "Intellectual history on a high order ... and very exciting." —The New York Times In this wide-ranging, intellectually vigorous study, Said traces the origins of "orientalism" to the centuries-long period during which Europe dominated the Middle and Near East and, from its position of power, defined "the orient" simply as "other than" the occident. This entrenched view continues to dominate western ideas and, because it does not allow the East to represent itself, prevents true understanding. Source: Publisher
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Only Skin Deep: Changing Visions of the American Self - Fusco, Coco; Wallis, Brian (Abrams and International Center of Photography, 2003)
"By bringing together a provocative selection of essays and images, Only Skin Deep: Changing Visions of the American Self addresses the issues of nation, race, and selfhood and how they are depicted in ways that are challenging and informative, prompting readers to consider the impact of photography on our everyday lives." "If photographs are chiefly responsible for perpetuating myths of American identity, can a different reading of these representations break down distorting stereotypes? This is the central question posed by Only Skin Deep. The authors in this book forcefully argue that race and nation - and, indeed, photography itself - are fictions, cultural constructions that shape our social interactions. Even as symbols, these photographic depictions of ethnic difference and cultural superiority have very real consequences. This collection of works and essays addresses, for example, the lingering consequences of American colonial expansion; the conflict between public and private visualizations of individuals; the role of commercial imagery in shaping gender roles; the impact of fantasy in ethnic or ethnographic photography; and the uses of science to provide justification for politicized depictions of "race."" "Accompanying a major exhibition of the same name, Only Skin Deep offers a critical rereading of the archive of the history of photography. This applies to the works of famous photographers - such as Dorothea Lange, Walker Evans, Ansel Adams, and Edward Steichen - as well as lesser-known historical figures, including Charles Eisenmann, Frances Benjamin Johnston, Will Soule, and Toyo Miyatake. A substantial part of the book is devoted to contemporary artists and photographers who have moved beyond the multicultural approach to representations of "race" and have made an investigation of the semiotics of cultural identity a prevalent theme over the past decade. Among the recent photographers included are: Nancy Burson, Nikki S. Lee, Glenn Ligon, Paul Pfeiffer, Hulleah Tsinhnahjinnie, Cindy Sherman, Lorna Simpson, and Andres Serrano."--(BOOK JACKET)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

African American Art and Artists - Lewis, Samella (University of California Press, 2003)
Samella Lewis has brought African American Art and Artists fully up to date in this revised and expanded edition. The book now looks at the works and lives of artists from the eighteenth century to the present, including new work in traditional media as well as in installation art, mixed media, and digital/computer art. Generously and handsomely illustrated, the book continues to reveal the rich legacy of work by African American artists.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Ain't I a Woman Black Women and Feminism - hooks, bell (Routledge, 2015)
This landmark work of history and theory challenges every accepted notion about the nature of black women’s lives. Ain’t I A Woman examines the impact of sexism on black women during slavery, the historic devaluation of black womanhood, black male sexism, racism within the recent women’s movement, and black women’s involvement with feminism. hooks refutes the antifeminist claim that black women are not victims of sexist oppression nor in need of an autonomous women’s movement. She pushes feminist dialogue to new limits by claiming that all progressive struggles are significant only when they take place within a broadly defined feminist movement which takes as its starting point that race, class, and sex are immutable facts of human existence. bell hooks’ insight as a black woman and a feminist extends the scope of feminist theory and practice for us all, and marks the emergence of a revitalized feminism in the 1980s.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Black Looks: Race and Representation - hooks, bell (Routledge, 2015)
"In the critical essays collected in Black Looks, bell hooks interrogates old narratives and argues for alternative ways to look at blackness, black subjectivity, and whiteness. Her focus is on spectatorship--in particular, the way blackness and black people are experienced in literature, music, television, and especially film--and her aim is to create a radical intervention into the way we talk about race and representation. As she describes: 'The essays in Black Looks are meant to challenge and unsettle, to disrupt and subvert.' As students, scholars, activists, intellectuals, and any other readers who have engaged with the book since its original release in 1992 can attest, that's exactly what these pieces do"(Provided by publisher)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

L'Atlantique noir: modernité et double conscience - Gilroy, Paul (Éditions Amsterdam, 2010)
Qu'est-ce que l'identité noire ? Contre ceux qui en défendent une conception ethniciste ou nationaliste, ou qui cherchent avant tout à en préserver l'authenticité, Paul Gilroy montre comment cette identité complexe, nourrie d'une diversité irréductible, repose sur l'existence d'un espace transnational en constante transformation, qui n'est pas spécifiquement africain, américain, caribéen ou britannique, mais tout cela à la fois : l'Atlantique noir. L'objet de ce livre est de donner à voir l''existence de cet espace constitué dès le XVIIe siècle à travers l'histoire de la traite négrière, de retracer ce réseau serré de relations, d'échanges à multiples sens, d'idées, d'hommes et de productions culturelles. Au fil de pages peuplées par les figures les plus hétéroclites, de Spike Lee à Walter Benjamin en passant par les Jubilee Singers, Richard Wright, W. E. B. Du Bois, Jimi Hendrix, Wynton Marsalis et Hegel, l'espace et le temps singuliers de l'Atlantique noir prennent forme et consistance de façon saisissante. La musique, mode d'expression de prédilection d'une culture enracinée dans l'expérience des terreurs indicibles de l'esclavage, avec ses usages et ses allers-retours inattendus d'un bord à l'autre de l'Atlantique, joue ici un rôle de premier plan. Le retour sur l'esclavage et son caractère intrinsèquement moderne, opéré dans les oeuvres de nombreux écrivains noirs, ouvre par ailleurs à une relecture critique de la modernité, d'une portée universelle, au même titre que la critique des conceptions figées et réductrices de l'identité.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Race and History: Selected Essays 1938-1988 - Franklin, John Hope (Louisiana State University Press, 1992)
John Hope Franklin, one of the US's foremost historians, collects twenty-seven of his most influential shorter writings. The essays are presented thematically and include pieces on southern history; significant but neglected historical figures; historiography; and the connection between historical problems and contemporary issues.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Collecting African American Art: the Museum of Fine Arts, Houston - Franklin, John Hope; Wardlaw, Alvia J (Museum of Fine Arts ; Yale University Press, 2009)
This important book showcases institutional and private efforts to collect, document, and preserve African American art in American's fourth largest city, Houston, Texas. Eminent historian John Hope Franklin's essay reveals his passionate commitment to collect African American art, while curator Alvia J. Wardlaw discusses works by Robert S. Duncanson, Henry Ossawa Tanner, Horace Pippen, and Bill Traylor as well as pieces by contemporary artists Kojo Griffin and Mequitta Ahuja. Quilts, pottery, and a desk made by an African American slave for his daughter contribute to the overview. The book also focuses on the collections of the "black intelligentsia," African Americans who taught at black colleges like Fisk University, where Aaron Douglas founded the art department. A number of the artists represented were collected privately before they were able to exhibit in mainstream museums.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Méthodologie de recherche décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Videogames about Politics as States of Exception - Hao, Yu (Gamevironments, 2020)
This article looks at videogames about politics within the theoretical framework of Giorgio Agamben’s states of exception and argues that while videogames can reveal political issues by implementing rules into the gameplay, they simultaneously render the in-game rules and consequences inoperative in regard to real-world politics, which can be described as states of exception in Agamben’s sense. Agamben distinguishes between the fictitious and the real state of exception, and this distinction leads to his proposal of a politics of pure means in which he considers play as a means of profanation that renders what has been played with inoperative and free. Drawing on this discussion, the article looks at the parallel between the rules in videogames and the laws in states of exception and re-examines the concepts of game rules and play under the rubric of Agamben’s political philosophy. In so doing, it explores how playing with rules in videogames about politics can turn these games into states of exception to talk about and reflect on various political issues.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 5-Auteur.rice PANDC; _Nettoyé

The International Encyclopedia of Media Studies: Media History and the Foundations of Media Studies - Valdivia, Angharad N.; Nerone, John C.; Mayer, Vicki; Mazzarella, Sharon R.; Parameswaran, Radhika E.; Scharrer, Erica; Darling-Wolf, Fabienne; Gates, Kelly (Wiley-Blackwell, 2013)
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Lyrical Nationalism: Gender, Friendship, and Excess in 1970s Hindi Cinema - Jha, Priya (The Velvet Light Trap, 2003)
In this essay I examine one particular feature of the films, the song-and-dance sequences, as they draw attention to the fractious nature of the postcolonial nation while simultaneously attempting to construct a space for the articulation of a consolidated national identity.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

History First-Hand: Memory, the Player and the Video Game Narrative in the Assassin's Creed Games - Menon, Lakshmi (Rupkatha Journal on Interdisciplinary Studies in Humanities, 2015)
This paper will look at the convergence of the interactive free flow of video games and the questioning and revisioning of historical continuity using the example of the Assassin's Creed series by Ubisoft. With a story that exists simultaneously in the modern day and the 15th century, the games allow the player to take control of characters and alter, or make possible, events recognisable as historical fact. It plays with both history and memory and history as memory, as the life of the primary player character is being relived through the genetic memories of one of his descendants. Being highly narrative-bound, the Assassin's Creed games use, via the medium of the screen, the rift between history and memory as a central element of narrative, theme, and game design, which this paper will explore. Furthermore, using theories of convergence this paper will examine how video games provide a new, interactive mode of storytelling that is rapidly becoming representative of our age.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Game Studies India Adda Talk #8: Prabhash Tripathy - Game Studies India Adda (Game Studies India Adda, 2021)
What/Who is playing Cyborg: An investigation of the 'Gamer' as a figure - Prabhash Ranjan Tripathy The current talk is an exploration into the question as to whether the gamer figure that emerged in India in the 1990s can be thought of as a cyborg and if so, then what kind of cyborg is the gamer? Can one think of the gamer-cyborg as a posthuman liberatory figure or is the gamer-cyborg still all too human? The intent of the paper in asking these questions and problematizing the figure of the Gamer is to launch an investigation into the more pressing question that one encounter in the wake of the cyber/information-turn, that is, how does one contemplate, comprehend, and articulate the 'new' in the identities that are formed and acquired with the advent of what has been identified as the cyber/information turn in culture? Can the connection between biological and technological be the sole basis for considering figurations like the Gamer as something new? Can they be thought of as a new subjectivity, a new politics, a new relationship to power? Is this 'new' democratic, free of discrimination and based on an egalitarian principle or is the 'new' an optimization of old and existing structures and modes of oppression? Bio: Prabhash Ranjan Tripathy was born in Odisha, India. He completed his B.A. (Hons) English, M.A. in English literature and M.A. in Comparative Indian Literature from University of Delhi. He is currently a PhD scholar at the school of Arts and Aesthetics, Jawaharlal Nehru University. Has submitted his MPhil dissertation titled ‘Playing Cyborg: A study of the Gamer in the Videogame Parlours of Delhi and Mussoorie’, following which was a doctoral fellow at the International Research Centre “Interweaving Performance Cultures” and is currently working on his PhD dissertation titled ‘Between WorkStation and PlayStation: The Cultural Location of Videogames in India’. Interest areas include Superhero comic books, Anime, Video Games, Combat Sports, and Mythology. He is fascinated by felines and loves to trek, read, write, click and play.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Games Studies India Adda Talk #4: Poonam Chowdhury - Game Studies India Adda (Game Studies India Adda, 2021)
Thatgamecompany’s 'Journey' (2012) is a videogame like no other. This serene atmospheric game came out at a time when fast-paced, aggressive, AAA games were (and still are) the norm. Soon after the game’s release in 2012, thatgamecompany’s courage and hard work started getting the appreciation it deserved. 'Journey' has won several ‘Game of the Year’ awards and received several other awards and nominations, including a ‘Best Score Soundtrack for Visual Media’ nomination for the 2013 Grammy Awards. For this Game Studies India Adda Talk, I will be discussing (read: gushing over) this game’s brilliant visual and auditory art, wordless storytelling techniques, and one-of-a-kind multiplayer experience. Please join me on this talk and let's take a ‘journey’ like no other. Pun intended. Thank you and I hope you all have a wonderful new year. 🙂 Here’s the game trailer: https://www.youtube.com/watch?v=Ie4iz...
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

GSI Adda Talk #2 Riko Banerjee What is it like to be a Gamer or pursue Game Studies in India? - Game Studies India Adda (Game Studies India Adda, 2020)
Video gaming is one of the most popular hobbies in the world, with the gaming industry grossing more revenue than the movie and the music industry combined. The estimated number of gamers across the whole world as of August 2020 is 2.7 billion, which is more than one-third of the world population. The benefits of gaming, as cited by numerous researchers, include a boost in confidence, improved cognitive abilities, stress relief, improved problem-solving skills, enhanced social skills among dyslexic kids, and among many others. Even though video gaming as a hobby and career is slowly getting recognition in India, majority of the population still scoff at the activity, shunning gamers and game researchers alike, citing out-of-context and sometimes even false media propaganda. The challenges faced by a typical gamer in India include lack of information, budget limitation, lack of support from parents and teachers when it comes to teenage gamers, and the overall lack of gaming as a mainstream culture among countrymen. As for someone who wants to pursue Game Studies, there is currently little to no provision for that due to the tightly knit education system in the country and the utter lack of educational institutes offering courses on game studies. We go on to further discuss all of the above challenges and experiences faced by a gamer or someone who wants to pursue game studies in India, in our detailed talk that is scheduled on November 21, 2020.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

First Person Encounters #5: Abhi, creator of Venba - Game Studies India Adda
Venba is a narrative cooking game, where you play as an Indian mom, who immigrates to Canada with her family in the 1980s. Players will cook various dishes and restore lost recipes, hold branching conversations and explore in this story about family, love, loss and more. More on Steam: https://store.steampowered.com/app/14.... Developer, Abhi, gives Game Studies India an exclusive preview talking about identity, nostalgia, memory and of course, food. In conversation with Poonam Chowdhury and Souvik Mukherjee.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

First-Person Encounters #4: Poornima Seetharaman - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our third podcast where we talk with Poornima Seetharaman. She is the first Indian to be inducted in the Women in Games (WIGJ) Hall of Fame and is also the lead game designer at Zynga. Hear as we talk about her foray in the world of gaming.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

First-Person Encounters #3: Prof. Xenia Zeiler - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our third podcast where we interview Xenia Zeiler, an associate professor of South Asian studies at the University of Helsinki, Finland. Her research is situated at the intersection of digital media, religion, and culture, with a focus on India and the worldwide Indian community.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

First-Person Encounters #2: Satyajit Chakaborty - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our second podcast where we interview Satyajit Chakraborty, a game developer, game designer and researcher. He also founded Flying Robots Studios in 2012 and has made various unique games. Here he talks about his first experiences with gaming in India.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

First Person Encounters #1: A Game Studies India Adda Podcast - Game Studies India Adda (2020)
The First Podcast in a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Crab-Rangoons in Kyrat: (Re)Writing South-Asian History in Far Cry 4 - Mukherjee, Souvik (Games and Culture, 2021)
Recent research has started focusing on the representation of history in videogames. Such representation is almost always of mainstream history and usually presented from a Western perspective. Set in a fictitious Himalayan kingdom in South Asia, Ubisoft’s Far Cry 4 is arguably a crucial example of how history is represented using Western and even colonial frameworks and where the narratives that do not emerge from conventional written history are almost always rendered invisible. Using the frameworks of Subaltern Studies and “border-thinking,” this essay attempts to unpack issues of Orientalism and “colonial difference”; it then engages with postcolonial digital humanities and postcolonial game studies to comment on how history is represented in videogames and how the neglected gaps and silences in the game are important in constructing the historiography in videogames. In the process, the essay engages in a debate with current notions of videogame-historiography.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Queerness in Play - Harper, Todd; Adams, Meghan Blythe; Taylor, Nicholas (Palgrave Macmillan, 2018)
"Queerness in Play examines the many ways queerness of all kinds - from queer as 'LGBT' to other, less well-covered aspects of the queer spectrum - intersects with games and the social contexts of play. The current unprecedented visibility of queer creators and content comes at a high tide of resistance to the inclusion of those outside a long-imagined cisgender, heterosexual, white male norm. By critically engaging the ways games - as a culture, an industry, and a medium - help reproduce limiting binary formations of gender and sexuality, Queerness in Play contributes to the growing body of scholarship promoting more inclusive understandings of identity, sexuality, and games."--Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Playing Subaltern: Video Games and Postcolonialism - Mukherjee, Souvik (Games and Culture, 2018)
The postcolonial has still remained on the margins of Game Studies, which has now incorporated at length, contemporary debates of race, gender, and other areas that challenge the canon. It is difficult to believe, however, that it has not defined the way in which video games are perceived; the effect, it can be argued, is subtle. For the millions of Indians playing games such as Empire: Total War or East India Company, their encounter with colonial history is direct and unavoidable, especially given the pervasiveness of postcolonial reactions in everything from academia to day-to-day conversation around them. The ways in which games construct conceptions of spatiality, political systems, ethics, and society are often deeply imbued with a notion of the colonial and therefore also with the questioning of colonialism. This article aims to examine the complexities that the postcolonial undertones in video games bring to the ways in which we read them.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Gaming Representation: Race, Gender, and Sexuality in Video Games - Malkowski, Jennifer; Russworm, TreaAndrea M. (Indiana University Press, 2017)
Gaming Representation' offers a timely and interdisciplinary call for greater inclusivity in video games. The issue of equality transcends the current focus in the field of Game Studies on code, materiality, and platforms. Journalists and bloggers have begun to hold the digital game industry and culture accountable for the discrimination routinely endured by female gamers, queer gamers, and gamers of color. Video game developers are responding to these critiques, but scholarly discussion of representation in games has lagged behind. Contributors to this volume examine portrayals of race, gender, and sexuality in a range of games, from casuals like Diner Dash, to indies like Journey and The Binding of Isaac, to mainstream games from the Grand Theft Auto, BioShock, Spec Ops, The Last of Us, and Max Payne franchises. Arguing that representation and identity function as systems in games that share a stronger connection to code and platforms than it may first appear, 'Gaming Representation' pushes gaming scholarship to new levels of inquiry, theorizing, and imagination.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créatrice; _Nettoyé

Videogames and Post-Colonialism: Empire Plays Back - Mukherjee, Souvik (Palgrave MacMillan, 2017)
This book focuses on the almost entirely neglected treatment of empire and colonialism in videogames. From its inception in the nineties, Game Studies has kept away from these issues despite the early popularity of videogame franchises such as Civilization and Age of Empire. This book examines the complex ways in which some videogames construct conceptions of spatiality, political systems, ethics and society that are often deeply imbued with colonialism. Moving beyond questions pertaining to European and American gaming cultures, this book addresses issues that relate to a global audience ? including, especially, the millions who play videogames in the formerly colonised countries, seeking to make a timely intervention by creating a larger awareness of global cultural issues in videogame research. Addressing a major gap in Game Studies research, this book will connect to discourses of post-colonial theory at large and thereby, provide another entry-point for this new medium of digital communication into larger Humanities discourses.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

The Playing Fields of Empire: Empire and Spatiality in Video Games - Mukherjee, Souvik (Journal of Gaming & Virtual Worlds, 2015)
As in historical accounts, empire in video games too is concerned with the acquisition of geographical space. Like the splash of red marking the stretch of the British Empire on Victorian world maps, video games that let one play at empire are also obsessed with stamping the imperialist authority of ‘your’ nation on their in-game maps. Video game empires too work on the necessary logic of spatial expansion connected with which is the necessity to remove the ‘fog’ which prevents the player’s ‘line of sight’ from accessing information about surrounding areas. The focus on cartography and surveying in British Raj India is a useful comparison. Although much scholarship exists around the representations of the spatiality of Empire in more traditional media, there is little that addresses the video game representations of Empire. This article is about the representation and experience of space in conceptions of Empire vis-à-vis in empire-building video games, as understood in terms of both cartography and the lived experience of space. It argues that although empire-building video games are largely framed within the western imperialist discourses, the very nature of gameplay itself challenges these set notions – in a way remediating the ambiguity and anxieties of the representations of empire and its spatial constructs in earlier media.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Critical media studies, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play -- the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

A Critical Interpretation of a New “Creative Industry” in Turkey: Game Studios and the Production of a Value Chain - Binark, Mutlu; Bayraktutan, Günseli (Computer Games and New Media Cultures: a Handbook of Digital Games Studies, 2012)
In this chapter, the creation of a value chain during the process of digital games development in Turkey is discussed using a critical political economy approach. This study claims to be the first of its kind that intends to examine the topography of the digital game industry in Turkey and gives a brief history and describes the present status of digital games production in Turkey. All the components of a value chain, namely, the industrial structure and development process, publishing and licensing, distribution and marketing structure, labor force, legal regulations, and governmental policies will be considered in that order to map out the present topography of the industry. The final part of the study will deal with possible solutions for further development in the industry. At this point, the study stresses the fact that all components of the value chain must be performed uninterrupted if the actors in Turkey’s digital game industry desire to position themselves as “producers” in global or local markets.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Video Games in Asia - Ng Wai-ming, Benjamin (The Video Game Explosion: a History from Pong to Playstation and Beyond, 2008)
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

The Video Game Explosion: a History from Pong to Playstation and Beyond - Wolf, Mark J. P. (Greenwood Press, 2008)
Video games have become a limitless and multifaceted medium through which major corporations and Hollywood visionaries alike are reaching broader global audiences and influencing cultural trends at a rate unmatched by any other media. This book traces the growth of a global phenomenon that has become an integral part of popular culture.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 5-Auteur.rice PANDC; _Nettoyé

Japanese Video Games in Singapore: History, Culture and Industry - Ng Wai-ming, Benjamin (Asian Journal of Social Science, 2001)
Globalization of Japanese popular culture is reshaping the global cultural landscape. Some forms of Japanese popular culture (such as video games animation and sushi) are well-received internationally, whereas others (such as pop music, films and TV dramas) are only popular in Asia. Of all forms of Japanese popular culture, video game is perhaps the most powerful due to its strong universal appeal. It has dominated the world market since the mid-1980s. This article uses Singapore as a case study to demonstrate the global popularization of Japanese video games. There has been a boom of Japanese popular culture in Singapore in the 1990s. In particular, Japanese video games, comics and animation have become an integral part of youth culture in Singapore (Ng, March 2000: 234-246; Ng, May 2000: 44-56; Ng, June 2000: 1-14). Video game is a neglected topic in cultural studies. Although there are some basic studies of Japanese video games in the Western world (Hayes & Disney, 1995; Herz, 1997; Kinder 1991; Monopolies, 1995; Sheff, 1993), its impact in Asia is largely unknown. This article is a preliminary study of the Japanese video game culture and industry in Singapore from historical and socio-cultural perspectives, focusing on consoles, games and players. Based on interviews, questionnaires and data from newspapers and magazines, this research aims at pro viding a general overview of the history and impact of Japanese video games in Singapore. All the data and analyses are basic and this is beyond the scope of this paper to discuss any particular issue or theory in details. This paper consists of four sections. The first three sections outline the development of home video game consoles, handheld electronic games and game arcades respectively. The concluding section pinpoints the characteristics of the video
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Multiculturalismo y crítica postcolonial: la diáspora artística latinoamericana (1990-2005) - Marín Hernández, Elizabeth (Universitat de Barcelona, 2005)
La presencia del arte contemporáneo latinoamericano en el mundo contemporáneo, es concebida y movilizada a través de la existencia de una diáspora que ha perdido toda clase de arraigo en sus lugares territoriales definitorios. Los lenguajes que éstas muestran tienden ha consolidar un gusto por la simultaneidad, por la complejidad, por lo marginal, por lo oculto, y por las relativizaciones de una realidad que se pregunta constantemente por el sentido de su ser. Las diásporas artísticas ubican sus propuestas en medio de una serie de posicionamientos, para tratar de narrar las historias y las situaciones, que comenzaron ha emerger, en el momento en el cual se establece una dominante epocal, observadora y tolerante de la diversidad de los márgenes. El arte de las diásporas parecía configurar un nuevo espacio de representación, digno de ser atrapado o explicado dentro de nuevas posiciones teóricas, que manifestarán el por qué de unas de estas expresiones, muchas veces imposibles de traducir ante la pérdida del sentido del monopolio cultural occidental en el campo de las artes. De allí que, se hallan confeccionado en el mundo contemporáneo tardocapitalista y posindustrial, posiciones teóricas que incluyentes y estudiosas de la alteridad, de las diferencias, de la otredad, de la subalternidad. Para partir de los enunciados fragmentarios y múltiples mostrados por las teorías multiculturalistas y por la Crítica Poscolonial. Un intento de dotar de sentido a una realidad global, que ha perdido las fronteras. En este sentido, el espectro teórico que estudia a la diversidad observa a las culturas, a sus contaminaciones y desplazamientos desde diversas perspectivas, las cuales han incido en el mundo del arte contemporáneo en la formulación de un Nuevo Internacionalismo incluyente de las representaciones de los otros. El arte latinoamericano en este contexto se encuentra convocado, invitado, para legitimar la puesta en escena de unas realidades que pretenden ser cercanas, y a su vez alejadas, por las tensiones producidas por las propuestas discursivas del multiculturalismo y del poscolonialismo, en sus lecturas sobre las culturas como opuestas y no como parte integrante de una metacultura global. Las diásporas se ubican a partir de la deconstrucción de los postulados mayores de estas nuevas tendencias teóricas, para evidenciar su localidad desde la particularidad de sus legados e historias. Espacio en el cual, los artistas pertenecientes a la diáspora contemporánea, han demostrado responder con presteza a la cantidad de situaciones presentadas en medio de una realidad interconectada desde tiempos anteriores, y que en la actualidad manifiesta la exacerbación de las relaciones con lo que se pretende diferente.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

The “Law and Order” of Violence Against Native Women: A Native feminist Analysis of the Tribal Law and Order Act - Robertson, Kimberly (Decolonization: Indigeneity, Education & Society, 2016)
In this essay, I aim to engage the growing body of scholarship that employs Indigenous feminist theories to understand and mobilize against the sexual and gendered violence committed against Native peoples. To accomplish this, I construct a Native feminist analysis of the 2010 Tribal Law and Order Act. I posit that despite the overwhelmingly positive characterizations of the legislation as “historic” in its potential to address violence against Native women and reduce crime in Indian country, a Native feminist reading of the Tribal Law and Order Act illuminates the degree to which the Act emerges from, engages with, and advances settler colonial and heteropatriarchal logics that cause violence against Native women in the first place. I suggest that although the Act does contain measures that have the potential to alleviate the experience of violence in Native women’s lives, it also diminishes tribal sovereignty, perpetuates the ongoing encroachment of tribal jurisdiction, regulates the boundaries of Native identity, and limits our ability to envision and enact practices of decolonization.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé